Domestic and International Experience in Researching Police Officers’ Motivation (Law and Safety, 2021)
The article is focused on the consideration of the motivation of police officers of the National Police of Ukraine as determinants of professional efficiency. The authors have analyzed the domestic and international experience of studying the professional motivation of police officers and the possibilities of its practical use in the system of psychological provision of the employees of the National Police of Ukraine. The levels and components of motivation, directions of its improvement have been studied. The authors have accomplished review of research on the motives for choosing a service in the police as a profession, as well as the factors of further motivation of the employees. The relationship between individual motivation, learning productivity, work and police officers’ satisfaction with the work has been traced. The role of self-motivation and self-organization in increasing the efficiency of professional activity has been determined.Motivating factors have been provided – achievement, recognition, responsibility, promotion and growth, etc., means to support motivation, as well as demotivators – stress due to internal factors, poor health and physical well-being, a negative example of employees who lost interest in the service, etc. The importance of organizational justice and personal example of the head, his awareness and attention to the factors of individual motivation and productivity of the employee for the optimization of the police activity has been substantiated.The perspective of developing diagnostic tools and development of motivation of police personnel in the field of work with psycho-technologies of diagnostic, therapeutic, normative and influential orientation has been outlined.
Keywords: professional motivation, motives for choosing a profession; motivational sphere of police officers; motivation; motivation technology.